2021
DOI: 10.1177/15353702211007084
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of molecular hydrogen on lung injury from lung transplantation

Abstract: Lung grafts may experience multiple injuries during lung transplantation, such as warm ischaemia, cold ischaemia, and reperfusion injury. These injuries all contribute to primary graft dysfunction, which is a major cause of morbidity and mortality after lung transplantation. As a potential selective antioxidant, hydrogen molecule (H2) protects against post-transplant complications in animal models of multiple organ transplantation. Herein, the authors review the current literature regarding the effects of H2 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Because organ transplantations, such as those of the lungs, heart, and kidneys, are closely related to IR injury, the success rate of transplantation depends on the extent to which IR injury is suppressed 33 , 34 . According to previous reports, the administration of hydrogen gas has been proven effective in suppressing IR injury after liver and lung transplantation 35 , 36 , and hydrogen is very effective for successful organ transplantation 37 , 38 . Filling the lumen with hydrogen also protected the intestinal tract from IR injury after transplantation 39 , 40 .…”
Section: Discussionmentioning
confidence: 98%
“…Because organ transplantations, such as those of the lungs, heart, and kidneys, are closely related to IR injury, the success rate of transplantation depends on the extent to which IR injury is suppressed 33 , 34 . According to previous reports, the administration of hydrogen gas has been proven effective in suppressing IR injury after liver and lung transplantation 35 , 36 , and hydrogen is very effective for successful organ transplantation 37 , 38 . Filling the lumen with hydrogen also protected the intestinal tract from IR injury after transplantation 39 , 40 .…”
Section: Discussionmentioning
confidence: 98%
“…This could be attributed to CCH continuously release hydrogen in mice, which can sustain anti-in ammatory effects in vivo. The anti-in ammatory mechanism of hydrogen is complex, the biological activity exhibited may be the combined effect of multiple mechanisms overlapping [18][19][20], so the relevant mechanism is not explored in depth in this manuscript. The mainstream theory suggests that hydrogen neutralizes the non-speci c effector molecule hydroxyl radicals and reduces oxidative loss or inhibits oxidative stress, thus regulating the oxidative stress signaling effect and exerting anti-in ammatory effects [21].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has suggested that H 2 exerts various biological effects, including anti-oxidative stress, anti-inflammation, anti-apoptosis and anti-pyroptosis [ 19 , 20 ], while regulating endoplasmic reticulum stress, and mitochondrial and immunological function [ 21 ]. Additionally, H 2 also modulates some intracellular signaling pathways, such as Nrf2/HO-1, NF-κB, MAPK, aquaporin-1 and aquaporin-5 [ 22 ]. Noda et al .…”
Section: Discussionmentioning
confidence: 99%